Effect of relaxation therapy on stress management among teenagers and adults - Afrin, Eshita Islam; Tany, Rajeka Fardosh (Dhaka University Journal of Biological Sciences, 2024)
The title of the present experiment is Effect of Relaxation Therapy on Stress Management Among Teenagers and Adults. The main purpose of the present experiment was to investigate the impact of relaxation therapy on stress reduction among teenagers and adults in Dhaka city. Utilizing purposive sampling, 30 participants (15 teenagers, 15adults) engaged in a 28-day relaxation program. The Bangla version of Life Stress Questionnaire and other stress management tools were used. Data were collected and analyzed by using ANOVA, t-test, and descriptive analysis. Results indicate a significant reduction in stress levels gradually across both groups for teenagers F for row(relaxation therapy) = 12.480, F for column(among participants) = 9.270 and for adults F for row(relaxation therapy) = 5.519, F for column(among participants) = 1.175 .The study also explores relationships between stress and various variables such as gender ,age, financial condition. Descriptive analysis showed that there was no significant difference between female and male but it reduced slowly for male (from 22.13 to 16.87) and for female (from 23.13 to 18.47) and decreased respectively in both financial groups for higher group (from 22.29 to 18.50) for lower group (from 22.94 to 16.94). The findings underscore the effectiveness of relaxation therapy in managing stress among adults and teenagers in Bangladesh. This study suggests the integration of relaxation therapy into stress management interventions and highlights avenues for future research in this area. Dhaka Univ. J. Biol. Sci. 33(2): 127-138, 2024 (July)